Analisis Industri Kreatif Dalam Memanfaatkan Identitas Kota Melalui Media Baru - Farid Rusdi; Gregorius Genep Sukendro (Jurnal Komunikasi, 2018)
Creative industry in Indonesia is growing rapidly cannot be separated from new media support. Utilization of new media by the creative industry attracts potential customers not only from domestic but also from abroad. They can get information about the creative industry through new media. The place where the creative industry is there is also a consideration for potential consumers in determining the choice. In this study aims to find out how the creative industry strategy communicates the attractiveness of the place where they are so that the interest of potential customers. This research will use marketing communication theory and new media. And in analyzing data obtained by researcher will use SOSTAC analysis. In addition to observation and literature study, researchers also conducted interviews with industry parties from two cities that are identical with the creative industries of Bandung and Yogyakarta, which has gained a reputation in overseas markets. From this research found that creative industry players have the potential to attract tourists, especially from abroad.  Industri kreatif di Indonesia berkembang pesat tidak bisa lepas dari dukungan media baru. Pemanfaatan media baru oleh industri kreatif menarik minat calon konsumen tidak hanya dari dalam negeri tapi juga dari luar negeri. Mereka bisa mendapatkan informasi tentang industri kreatif melalui media baru. Tempat di mana industri kreatif itu ada juga menjadi pertimbangan bagi calon konsumen dalam menentukan pilihannya. Penelitian ini bertujuan untuk mengetahui bagaimana strategi industri kreatif mengkomunikasikan daya tarik tempat di mana mereka berada sehingga menjadi daya tarik minat calon konsumen. Penelitian ini menggunakan teori komunikasi pemasaran dan media baru. Dan dalam menganalisis data yang diperoleh peneliti menggunakan analisis SOSTAC. Selain melakukan observasi dan studi pustaka, peneliti juga melakukan wawancara dengan pihak industri dari dua kota yang identik dengan industri kreatif yakni Bandung dan Yogyakarta yang sudah mendapat reputasi di pasar mancanegara. Dari penelitian ini ditemukan bahwa pelaku industri kreatif memiliki potensi untuk menarik minat wisatawan terutama dari luar negeri.